Improving Employee Performance Through Supporting Factors At San-Yu Frame Molding Industries Semarang Company (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to examine the factors that affect employee performance at San-yu Frame Molding Industries. The population in this study were 397 employees of the production department of San-yu Frame Molding Industries. With details of 205 permanent employees and 192 contract employees. The number of samples in this study was 51 people using purposive sampling method. data analysis tools using the SPSS program using multiple linear regression data analysis methods. The results of this study state that the three variables affect employee performance at San-Yu Frame Molding Industries Semarang. The results of regression calculations can be seen that the three variables have an influence on employee performance by 73.2%. While the remaining 26.8% is influenced by other variables. San-yu Frame Molding Industries in improving employee performance should pay attention to motivation, work environment, and employee discipline. this is because it has a major influence in improving work performance and productivity.